Brief Introduction of Az-Zaharawi’s Contributions in Science - Butt, Iqra (International Journal of Pathology, 2018)
History is full of description of great Muslim scientists and great patrons of sciences and research; however there is serious lack of awareness that keeps world not acknowledging their efforts and contributions to modern day sciences. Acknowledgment of their contributions will help nullifying the deliberate defamation of Islam and Muslims.